Trek: Real-Time Collaborative Travel Planner Mobile Application - Wong, WONG CAR SING; WAHID, DR. NORFARADILLA BINTI WAHID (Applied Information Technology And Computer Science, 2024)
This project develops Trek, a real-time collaborative travel planning mobile application that tackles the fragmented and inefficient nature of current trip planning tools, leading to smoother group coordination. Existing tools lack capabilities for real-time multi-user planning and updates, resulting in duplicated efforts, scheduling conflicts, and incomplete information sharing among groups planning trips together. Employing an incremental development model, iterative test-driven development, and technologies such as Flutter, Dart, MySQL and PHP, Trek focuses first on streamlined collaborative itinerary creation via mobile devices. The completed mobile application provides a comprehensive toolkit that simplifies travel organization for both individuals and groups, with features like budgeting, checklists, reminders, and document storage empowering seamless real-time collaboration. User testing yielded an average rating of 4.77 out of 5 stars, demonstrating Trek’s effectiveness in enhancing travel planning workflows. Future work may explore performance optimization for high user loads, offline capabilities, integration with travel booking services, and leveraging AI for personalized recommendations.